Implementasi Kebijakan Program Relaksasi terhadap Izin Mendirikan Bangunan di Kelurahan Bintaro Kecamatan Pesanggrahan Kota Jakarta Selatan - Mutiara Juliahisa Doneriani; Rahmat Salam (Politeknik Kampar, 2024)
The Relaxation Program in Bintaro Village is a policy to overcome obstacles in building construction permits. The aim of this research is to implement the IMB relaxation policy in Bintaro Village, South Jakarta. In this qualitative research, the South Jakarta Building Licensing Sub-Department and Bintaro Subdistrict demonstrated significant efforts in improving the effectiveness and efficiency of the licensing process. Implementation shows significant efforts from the South Jakarta City Administration Building Licensing Department and Bintaro Subdistrict, with certain aspects, such as Communication, Resources and Disposition having become the focus in assessing the success of this policy. Since the implementation of the IMB Relaxation Program in Bintaro Subdistrict, South Jakarta, interview results show a positive impact and effective policy implementation. Effective communication through various outreach activities has increased public understanding. Evaluation of human resources and redistribution of tasks as well as special training have been carried out to deal with the surge in demand for building permits. Although there are challenges regarding levy payments and community concerns about the financial burden, in general, the community accepts levy payments as a reasonable contribution to development. Recommendations for improvement include strategies to reduce administrative and financial burdens, maintaining a balance between development and community financial capacity. Overall, the implementation of the IMB Relaxation Program policy in Bintaro Subdistrict shows positive steps in increasing efficiency, transparency and community involvement in the building permit process.